Gender Gap: Family Support, Perceived Work Productivity and Job Satisfaction on Working from Home - Rahmi, Devi Yulia; Mardiah, Fatma Poni; Sufiawan, Nur Ari (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
The purpose of this study is to test whether family support has a positive effect on job satisfaction. In addition, to find out whether there was a gender gap in perceived work productivity and job satisfaction between men and women both before and during the Covid-19 pandemic and whether perceived work productivity and job satisfaction did not experience any difference both before the COVID-19 pandemic and after the occurrence of the COVID-19 pandemic. A quantitative approach was used to distribute questionnaires using a purposive sampling technique to 62 employees working from home in West Sumatera in 2021. Simple regression MANOVA was conducted to analyze the data. The result of the study found that family support and job satisfaction have a positive and significant effect. Another finding is that there was no gender gap in perceived work productivity and job satisfaction between men and women before and during the Covid-19 pandemic. In addition, there was no difference between job satisfaction and perceived work productivity, both before the Covid-19 pandemic and during the Covid-19 pandemic. The research implied that it assists companies and managers in making decisions and considering the sustainability of working-from-home programs for their employees and workers. In addition, companies and agencies are also asked to create an effective working-from-home model for women and men. Furthermore, it gives trust to families to continue supporting each other to create a healthy psychological environment when facing the COVID-19 pandemic. This study tries to see whether there are gender differences between men and women in terms of perceived work productivity and job satisfaction when working from home. The results of the different tests show this is different. This is also the case with the difference between conditions before and during Covid-19. It shows that there is no difference in perceived work productivity and job satisfaction between men and women.